Morgue of the Misbegotten: O’Neill’s Pattern of Salvation in The Iceman Cometh - Mufeed F. Al-Abdullah (European Journal of American Studies)
This paper analyzes Eugene O’Neill’s advocation of the impossibility of salvation or reformation on both societal and individual levels as dramatized in The Iceman Cometh. The method the playwright uses is to have a group of derelict characters gather in an isolated place and put them under the spell of a savior, Hickey, who aspires to shape their lives according to his own vision. O’Neill’s savior, however, proves to be a parody of a savior, who alienates the misfortunate group instead of saving it.Hickey’s brand of salvation leads to death as a means of terminating human life and negating spiritual values. This paper thus analyzes O’Neill’s masterpiece as a dramatization of his pessimistic vision of the world as a lodge of the misfortunate, of human life as a nightmare, and of death as the only way out. The Iceman Cometh orchestrates no hope for man in modern times, but sings an elegy for the misbegotten and depicts the world as a morgue for death-in-life.